Artemisia taurica Willd. var. vanensis Kursat & Civelek Asteraceae: Anthemideae , a new variety from Eastern Anatolia of Turkey - Kursat, Murat; Cıvelek, Semsettin; Sancar, Pelin Yılmaz; Turkoglu, Ismail (Ersin YÜCEL, 2018)
During our revisionary study on the taxa of the genus Artemisia L. Asteraceae distributed in Turkey, we came across two populations that we anticipated could be a new variety of the species Artemisia taurica Willd. belonging to the subgenus Seriphidium Besser Fourr. In the morphological and cytological studies, we found that the new variety should be included in the species A. taurica but it also has some considerable morphological differences. These morphological differences include the length of stems, peduncles, pistils, styles, forks of stigmas, stamens, filaments, and dimensions of leaves, phyllaries, corollas, ovaries, anthers, achenes, the direction of synflorescens branches, the orientation of the capitula on the synflorescens branches, colour of corolla, and the type of indumentum. The new variety was also different in terms of chromosome number. Based on these differences, we suggested that a new variety of the species A. taurica should be described, as A. taurica var. vanensis which is only distributed in a very limited area in the Eastern of Turkey. In this article, an identification key for all taxa in the subgenus Seriphidium and a rearranged description of the species A. taurica for including its two varieties, a diagnosis and an identification key for two sister varieties, a distribution map and a few descriptive figures of the new variety have been given

Türkiye'de yayılış gösteren Artemisia L. Asteraceae cinsinin taksonlarına yönelik yaptığımız revizyon çalışması sırasında, Seriphidium Besser Fourr. altcinsinde yer alan Artemisia taurica Willd. türünün yeni bir varyetesi olabileceğini tahmin ettiğimiz iki populasyonla karşılaştık. Morfolojik ve sitolojik çalışmalar neticesinde, bu yeni varyetenin A. taurica türüne dahil edilmesi gerektiğini, aynı zamanda bazı önemli morfolojik farklılıklara sahip olduğunu bulduk. Bu morfolojik farklılıklar; gövdelerin, kapitulum saplarının, pistillerin, situlusların, stigma çatallarının, stamenlerin, filamentlerin uzunlukları, yaprakların, fillarilerin, korollaların, ovaryumların, anterlerin, akenlerin boyutları, sinfloresens dallarının yönelimleri, kapitulumların sinflorosens dalları üzerindeki düzenlenişleri, corolla rengi ve tüy örtüsü tipini kapsamaktadır. Bu yeni varyete, kromozom sayısı bakımından da farklıydı. Bu farklılıklara dayanarak, Türkiye’nin doğusunda sınırlı bir alanda yayılış gösteren A. taurica türünün yeni bir varyetesinin A. taurica var. vanensis olarak tanımlanması gerektiğini önerdik. Bu makalede, Seriphidium altcinsindeki tüm taksonlar için bir teşhis anahtarı, A. taurica türünün iki varyeteyi de kapsayacak şekilde yeniden düzenlenmiş betimi, kardeş varyeteler için bir diyagnoz ve teşhis anahtarı, yeni varyetenin bir yayılış haritası ve birkaç tanımlayıcı resim verilmiştir
Artemisia taurica Willd. var. vanensis Kursat & Civelek Asteraceae: Anthemideae , Türkiye’nin Doğu Anadolu’sundan yeni bir varyete